Effect of 8 week endurance training on plasma and heart tissue collagen XVIII in male Wistar rats - حجت الله نیک بخت; احمد عبدی; خسرو ابراهیم (Shahid Beheshti University, 2012)
Purpose: the aim of this study was to examine the effect of endurance training on plasma and heart tissue collagen XVII in male Wistar rats. Methods: 16 male Wistar rats (4-6 week old. 125-135 g weight) were randomly divided two groups: experimental (n=8) and control (n=8) groups. Training protocol consisted of treadmill exercise at 20 to 60 min, speed 28 to 34 m٫min. (0%) grade, for 5days٫week for 8 weeks. Rats were sacrificed 72 h after the last session of exercise for measurement collagen XVIII levels in plasma and heart tissue. Plasma and tissue collagen XVIII levels measured using ELISA. Data were analyzed using independent t-test at P= 0.05. Results collagen XVIII levels increased in plasma and heart tissue after 8 weeks endurance training, but significant difference observed only in heart tissue (P=0.046). Conclusion: It likely appears that increased of collagen XVIII was indicator of exercise training effect on anti-angiogenesis and confirmed the anti-cancer impact of exercise training.